THE IMPACT OF MOTIVATION AND WORK SKILLS ON THE PERFORMANCE OF THE CREW ABOARD THE MV PEGASUS UNIX - Mohamad Arif Guntoro (International Journal Management and Economic, 2024)
This study aims to assess the impact of motivation and work ability on the performance of crew members (ABK) aboard the MV Pegasus Unix. Optimal performance of ABK is crucial for the success of ship operations and safety at sea, given the unique challenges and demanding work environment. A quantitative approach is employed in this study using a survey method to collect data from the ship's crew. The hypotheses examined are: (1) The effect of motivation on ABK performance, (2) The effect of work ability on ABK performance, and (3) The combined effect of motivation and work ability on ABK performance. This research is descriptive and quantitative, utilizing questionnaires for data collection. Data analysis is conducted with SPSS, involving descriptive statistical tests, classical tests, multiple linear regression analysis, and hypothesis testing. The study population consists of 71 ABK members from the MV Pegasus Unix in Jakarta. The data analysis results indicate that, individually, both work motivation and work ability impact ABK performance on the MV Pegasus Unix. Additionally, the independent variables (work motivation and work ability) together influence the performance of the ABK on the ship.